DEMOKRASI PANCASILA SEBAGAI POLITIK JALAN TENGAH INDONESIA - Anshari, Anshari (Muhammadiyah Makassar University, 2024)
ABSTRACTAs a state ideology, Pancasila must be the source of the order of life in the nation. In this case, the meaning of ideology itself is the science of ideas (the science of ideas). We can clearly see from this kind of understanding that Pancasila is an alternative or bridge that connects diversity into a fundamental value and can be integrated into any values, whether related to religion, customs and others. The presence of Pancasila Democracy is a middle way that needs to be approached wisely in order to realize unity between the various ethnic and cultural backgrounds of Indonesian society. In the basic context of the formulation or formation of national law, the existence of Pancasila democracy is no different from the existence of Pancasila itself as a state ideology whose values must be manifested in the legal sub-system or norms that apply in Indonesian society, whether related to political, economic, social norms. culture, public policy, especially in the form of legislation.Keywords: Pancasila, Democracy, Legal System, Indonesia